META-ANALYSIS OF THE EFFECT OF USE WORKSHEETS ON STUDENTS CRITICAL AND CREATIVE THINKING SKILLS IN LEARNING NATURAL SCIENCE IN JUNIOR HIGH SCHOOL AND PHYSICS IN SENIOR HIGH SCHOOL - Nadya Syahdi; - Desnita; - Murtiani; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2021)
This research is a meta-analysis of the influence of student worksheets on students' critical and creative thinking skills. Education currently uses the 2013 curriculum. The curriculum demands to learn that provides opportunities for students to develop all their potential. This meta-analysis study aims to determine the effect size value of the effect of using worksheets on students' critical and creative thinking skills based on education level, material unit, and learning model. The sample of this study used 20 national and international articles.  The articles used in this study have been analyzed and meet the categories for effect size calculations and are grouped based on three indicators. There are three group indicators analyzed, namely based on education level, based on material units, and based on learning models.  The results of this meta-analysis study are 1) Based on junior high and high school education levels, the effect of using student worksheets is equally effective against improving critical and creative thinking skills, but when compared to the effect size results, the SMA level has a higher value, 2) Based on the material unit,  fluid material units are more effectively used to improve critical and creative thinking skills, and 3) Based on the learning model, the cooperative learning model is effectively used to improve critical thinking skills and problem-solving is effective to improve students' creative thinking skills.